Erratum: The Cochrane Library and treatment of patent ductus arteriosus: an overview of reviews. Issue 1 (9th January 2013) - Harrold, J.; Lacaze‐Masmonteil, T.; Hartling, L.; Oleszczuk, M.
Abstract The above article was published in EBCH 7:1185–1195 (2012). DOI:10.1002/ebch.1855 Copyright © 2013 The Cochrane Collaboration. Published by John Wiley & Sons, Ltd. The Cochrane Collaboration